Regulating coordination number in atomically dispersed Pt species on defect-rich graphene for n-butane dehydrogenation reaction - Xiaowen Chen (Nature Portfolio, 2021)
Direct dehydrogenation has been a thematic research area resulting from the energy shortage and petroleum gas upgrading scenario. Here, the authors fabricate fully exposed Pt3 clusters and correlate dehydrogenation activity with average coordination number of Pt-Pt bond.